Sub-micron thick liquid sheets produced by isotropically etched glass nozzles. Issue 7 (2nd March 2022) - Crissman, Christopher J.; Mo, Mianzhen; Chen, Zhijiang; Yang, Jie; Huyke, Diego A.; Glenzer, Siegfried H.; Ledbetter, Kathryn; F. Nunes, J. Pedro; Ng, May Ling; Wang, Hengzi; Shen, Xiaozhe; Wang, Xijie; et al.
Abstract : Liquid sheet jet formation holds immense promise to provide a continuously replenished target for static structural biology and high energy density studies conducted in X-ray free electron laser, synchrotron, and pulsed electron facilities. Abstract : We report on the design and testing of glass nozzles used to produce liquid sheets. The sheet nozzles use a single converging channel chemically etched into glass wafers by standard lithographic methods. Operation in ambient air and vacuum was demonstrated. The measured sheet thickness ranges over one order of magnitude with the smallest thickness of 250 nm and the largest of 2.5 μm. Sheet thickness was shown to be independent of liquid flow rate, and dependent on the nozzle outlet area. Sheet surface roughness was dependent on nozzle surface finish and was on the order of 10 nm for polished nozzles. Electron transmission data is presented for various sheet thicknesses near the MeV mean free path and the charge pair distribution function for D2 O is determined from electron scattering data.